Digestion of sweet potato (Ipomoea batatas (L.) Lam) foliage in pigs. Ileal and fecal in vitro digestibility - D?az, Ivonne; Gonz?lez, C.; Reyes, J.; Car?n, Martha; Delgado, E.; Ly, Julio (Cuban Journal of Agricultural Science, 2013)
The ileal (pepsin/pancreatin) and rectal (fecal inoculum) in vitro digestibility of organic matter (OM) and N were determined in four samples of sweet potato (Ipomoea batatas (L.). Lam) foliage meal and was compared with that of soybean and maize. The ileal in vitro digestibility of DM and OM of the sweet potato foliage meal was of 40.6 and 40.3 %, respectively, while these same indexes at fecal level were of 46.4 and 51.0 %, respectively. The production of total short-chain fatty acids (P < 0.001) related, significantly, with the fecal in vitro digestibility of the OM (R2 1.000). It is suggested that the nutritive value of sweet potato foliage meal may be inversely proportional to its content in mineral material and cell wall. Key words: pigs, in vitro digestibility, pepsin, pancreatin, fecal inoculum, sweet potato foliage.